The activation domain of the bovine papillomavirus E2 protein mediates association of DNA-bound dimers to form DNA loops. - Knight, J D (1991)
The E2 transactivator protein of bovine papillomavirus binds its specific DNA target sequence as a dimer. We have found that E2 dimers, preformed in solution independent of DNA, exhibit substantial cooperativity of DNA binding as detected by both nitrocellulose filter retention and footprint analysis techniques. If the binding sites are widely spaced, E2 forms stable DNA loops visible by electron microscopy. When three widely separated binding sites reside on the DNA, E2 condenses the molecule into a bow-tie structure. This implies that each E2 dimer has at least two independent surfaces for multimerization. Two naturally occurring shorter forms of the protein, E2C and E8/E2, which function in vivo as repressors of transcription, do not form such loops. Thus, the looping function of E2 maps to the 161-amino acid activation domain. These results support the looping model of transcription activation by enhancers.